After The Deluge: Plant Revival Post-Flooding. (May 2019) - Yeung, Elaine; Bailey-Serres, Julia; Sasidharan, Rashmi
Abstract : Increasing flooding events have detrimentally impacted food security amid a growing global population. Complete submergence of plants represents the most severe flooding stress and studies have identified underwater responses to low oxygen and light availability. However, knowledge on plant responses during the post-submergence phase is limited. It is important to consider how plants can resume vegetative growth after enduring submergence and post-submergence stress. This review highlights current knowledge on physiological and molecular adaptations following desubmergence. Interplays of reactive oxygen species (ROS), energy depletion, photoinhibition, desiccation stress, and hormonal signaling have been characterized as components of the post-submergence stress response. Active elucidation of key genes and traits enhancing post-submergence adaptations is highly relevant for the improvement of submergence tolerance and ultimately crop yield. Highlights: Recovery of submergence is critical to the flooding tolerance of nonaquatic plants. Post-submergence phase challenges include energy deprivation, oxidative stress, dehydration, photoinhibition, and premature senescence. There is genetic variation in post-submergence recovery. Post-submergence stress management strategies include limiting oxidative stress through antioxidant activity and other means, photosynthesis recovery, control of water loss, and other metabolic acclimations. Hormones coregulate recovery responses but details of their interactions are underexplored.